تقييم مجموعة من الطرز الوراثية المدخلة للفول العادي vicia faba تحت ظروف المنطقة الساحلية - قبيلي صالح; خطاب نائل; احمد طارق (Latakia University Journal -Biological Sciences Series, 2013)
أجري تقييم تسعة طرز وراثية مدخلة من الفول العادي vicia faba هي: (flip84-59fb, AGUADOLCE LB 1266 SML,، FLIP84-14FB، GIZE. 461, REINA BLANCA، البلدي، القبرصي، الاسباني). خلال موسمي الزراعة (2010-2011 و2011-2012 (في مزرعة البصة قرب مدينة اللاذقية. لاعتماد المتفوق منها إنتاجيا كأصناف محسنة عالية الإنتاجية في تلك المنطقة، إضافة لاستخدام بقية الطرز المتميزة بصفات معينة كأصول وراثية اعتماداً على الصفات التي تتفوق بها على الطرز المحلية لإدخالها في برامج تربية مستقبلاً. أشارت نتائج الدراسة إلى وجود فروقات معنوية بين صفات الطرز المدروسة حيث تفوق الطراز الاسباني على جميع الطرز المدروسة بطول القرن (17.16 سم)، وترافق ذلك مع درجة توريث عالية (68.24) تلاه الطرازfilp84-59fb (15.1 سم)، وبوزن البذور بالقرن الواحد (33.6غ)، وذلك مع درجة توريث عالية (68.45) يليه الطراز القبرصي بوزن البذور بالقرن الواحد (14.66غ)، وبعدد البذور بالقرن (4.6)، وترافق ذلك مع درجة توريث منخفضة (23.53) تلاه الطرز (البلدي، والقبرصي، وaguadolce.lb1266، وfilip84-14fb) بعدد البذور بالقرن (3.6). تميز الطراز القبرصي على جميع الطرز بوزن القرن (23.43غ)، وتزامن ذلك مع درجة توريث عالية (76.45)، وبوزن البذرة الواحدة (3.93غ)، وذلك مع درجة توريث عالية (54.82)، يليه الطراز الاسباني بوزن القرن (20.63غ)، ثم الطراز filip84-59fb بوزن البذرة الواحدة (3.73غ)، وبوزن 100 بذرة (401غ)، وترافق ذلك مع درجة توريث عالية (97.49) يليهaguadolce.lb بوزن 100 بذرة (285غ)، وكان الطرازsml أكثر الأصناف تبكيرا حيث بلغ عدد الأيام حتى الأزهار (46 يوم) والنضج (148 يوم) يليه الطراز القبرصي (51 يوم) للإزهار والطرازflip84-59fb (155يوم) للنضج. An assessment of nine vicia faba genotypes (flip84-59fb, AGUADOLCE LB 1266 SML, FLIP84-14FB, GIZE.461, REINA BLANCA, autochthon, Spanish, and Cypriotes) was achieved, during 2010-2011 and 2011-2012 seasons, in Al_Bassa farm, near Lattakia city. Superior genotypes will be adopted as a high yield improved varieties in that area, however, the other genotypes (possessing genetic characteristics, superior of local genotypes), will be used in future breeding programs. The results indicated a significant differences between studied characteristics of the genotypes, as Spanish genotype recorded the best pod length (17.16cm), having high degree of inheritance (68.24), followed by filp84-59fb genotype (15.1 cm), with weight seeds per pod (33.6 g), having high degree of inheritance (68.45), followed by the Cypriot genotype, by seed weight (14.66 g), number of pod (4.6), having low degree of inheritance (23.53), followed by Cyprian autochtone genotype, and Aguadolce.lb1266,and filip84 -14fb number of pod (3.6). The Cypriot genotype was the best, in terms of pod weight (23:43 g), having high degree of inheritance (76.45) followed by Spanish (20.63g), and seed weight (3.93g), having medium degree of inheritance (54.82), followed by style filip84-59fb (3.73 g), and 100-seed weight (4.1g), having high degree of inheritance (97.49), followed by Aguadolce genotypes (285 g). The SML genotype is the best among premature genotypes in terms of flowering (46 days) and maturity (148 days), followed by Cypriot in terms of flowering (51 days) and flip84-59fb in terms of maturity (155 days).